Effect of fermented gambir (Uncaria gambir) leaves on broiler performance and blood lipids (Asian Journal of Agriculture, 2025)
Abstract. Widjastuti T, Faadhilah A, Adriani L. 2025. Effect of fermented gambir (Uncaria gambir) leaves on broiler performance and blood lipids. Asian J Agric 9: 615-622. Increasing broiler chicken productivity must be supported by proper management during rearing. Efforts to maintain production efficiency with potential alternatives to replace antibiotic growth promoters (AGP) include gambir leaves (Uncaria gambir). Fermented gambir leaves aim to improve performance and reduce blood lipid levels in broiler chickens, serving as an alternative ingredient to replace antibiotic growth promoters. The leaves are fermented with Lactobacillus plantarum at 1.5% and Rhizopus oligosporus at 1%. The study used a completely randomized design (CRD) with five treatments and four replicates. R0: 100% basal diet; R1: 100% basal diet + 0.5% fermented gambir leaf product; R2: 100% basal diet + 1% gambir leaf fermentation product; R3: 100% basal diet + 1.5% fermented gambir leaf product; R4: 100% basal diet + 2% gambir leaf fermentation product. Parameters measured included performance, blood, and meat lipid levels. Results showed significant differences (P
Keywords: Blood lipids, fermentation, gambir leaves, meat lipids, performance